A summability factor theorem for absolute summability involving almost increasing sequences - B. E. Rhoades; Ekrem Savaş (International Journal of Mathematics and Mathematical Sciences)
We obtain sufficient conditions for the series ∑anλn to be absolutely summable of order k by a triangular matrix.